2016
DOI: 10.1002/pola.28115
|View full text |Cite
|
Sign up to set email alerts
|

P4VP and oligo(phenylenevinylene)-perylenebisimide mixed donor-acceptor supramolecular comb polymer complexes with improved charge carrier mobility

Abstract: Random donor‐acceptor (D‐A) supramolecular comb polymers were formed when hydroxyl functionalized donor and acceptor small molecules based on Oligo(phenylenevinylene) (named OPVCN‐OH) and Perylenebisimide (named UPBI‐PDP), respectively, were complexed with Poly(4‐vinyl pyridine) (P4VP). A series of random D‐A supramolecular comb polymers were formed by varying the ratios of UPBI‐PDP and OPVCN‐OH with P4VP. A 100% P4VP‐donor polymer complex [P4VP(OPV1.00)] and a 100% P4VP‐acceptor polymer complex [P4VP(UPBI1.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Mesomorphic behavior observed in the pristine molecules was retained in the complexes P4VP‐PBI and P4VP‐NBI which was confirmed by POM and WXRD. Previous findings from our group also supports the observation that multiple sites of interaction, as is possible along the P4VP polymer backbone, can make up for the lack of strong individual point sites of interaction, resulting in overall improvement in alignment. The WXRD studies of the complexes versus pristine systems clearly demonstrated stretching of the rylenebisimide molecules due to hydrogen‐bonded intercalation of P4VP polymer chains.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Mesomorphic behavior observed in the pristine molecules was retained in the complexes P4VP‐PBI and P4VP‐NBI which was confirmed by POM and WXRD. Previous findings from our group also supports the observation that multiple sites of interaction, as is possible along the P4VP polymer backbone, can make up for the lack of strong individual point sites of interaction, resulting in overall improvement in alignment. The WXRD studies of the complexes versus pristine systems clearly demonstrated stretching of the rylenebisimide molecules due to hydrogen‐bonded intercalation of P4VP polymer chains.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to the soft supramolecular gel networks, bulk materials formed by supramolecular networks are seldom explored. In the recent years, the self‐assembly of P4VP with small π‐conjugated molecules was explored for their improvement in charge transport ability afforded by the enhanced π–π interactions . High degree of ordering of the semiconducting material could be achieved via the multiple hydrogen bonding interaction sites afforded by the P4VP.…”
Section: Introductionmentioning
confidence: 99%